Energy Dynamics in Eucalyptus tereticornis Smith Plantations in Western Uttar Pradesh - Singh, R. P. (Indian Forester, 1980)
The most energy rich component is the leaves in all the age groups. On per tree basis, energy storage increases with the increasing age of the plant and the maximum accumulation occurs in the individuals of nine year old stand of E.tereticornis. Total energy content, on per tree basis, of the hole, branches, leaves and root also tend to increase with increasing age. In all the age groups, hole retains maximum energy followed by root, branches and leaves. On area basis also standing crop of energy increases with advancing in age, being minimum in the year old individuals and maximum in nine year old stand. Leaf litter is more rich in energy content than non-leaf litter. Total amount of energy content in litter fall gradually increases in old stands. The amount of energy returned to to the soil through litter fall is 2.7; 6.2; 6.1; 3.4 and 2.7 per cent respectively, in corresponding age groups (5 to 9 years). Rate of energy fixation of E.tereticornis also increases with the age. E. tereticornis is more efficient than other tree species and its energy conserving efficiency ranges from 0.68 to 1.65 per cent.